Script concordance test in medical schools in Brazil: possibilities and limitations - Roberti, Alexandre; Roberti, Maria do Rosário Ferraz; Pereira, Edna Regina Silva; Costa, Nilce Maria da Silva Campos (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Routine use of the script concordance test (SCT) is not common in Brazilian universities. This study aimed to analyze application of the SCT in the medical school of a Brazilian university. DESIGN AND SETTING: Quantitative, analytical and descriptive study in the medical school of a Brazilian university. METHODS: A total of 159/550 students participated. The test comprised ten clinical cases within internal medicine, with five items per case, rated on a five-point Likert scale. The test was scored in accordance with a marking key that had been validated by a reference panel. RESULTS: In the pre-clinical and clinical phases, the mean scores were 51.6% and 63.4% of the maximum possible scores, respectively. Comparison of the means of the responses among all the years showed that there were significant differences in 40% of the items. The panel marked all the possible answers in five items, while in one item, all the panelists marked a single answer. Cronbach’s alpha was 0.64. The results indicated that the more senior students performed better. Construction of an SCT with discriminative questions was not easy. The low reliability index may have occurred due to: a) problems with the construction of the questions; b) limitations of the reference panel; and/or c) the scoring key. CONCLUSION: This instrument is very difficult to construct, apply and correct. These difficulties may make application of an SCT as an assessment method unfeasible in units with limited resources.